Endodontic Treatment During Pregnancy: Knowledge of General Dental Practitioners and Interns in Zliten, Libya - Mehdawi, Idris; Abdulrzag Gajoum,; Walid Benbubaker, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted to assess the knowledge of dental interns and general dentists about providing endodontic treatment to pregnant patients in Zliten-Libya. A descriptive, cross-sectional study was conducted using self-administered, closed ended questionnaire which was circulated among 127 dental interns and general dentists in Zliten-Libya. The questionnaire included demographical items and questions relative to the participant's knowledge regarding the endodontic treatment during pregnancy. The analysis of data was carried out using SPSS 26. 84% of survey participants indicated the second trimester as the safest period for endodontic treatment. 95% of respondents considered the need for a specific chair position among which 58% identified the correct one. 72% and 65% of respondents indicated the safety of local anaesthetics with vasoconstrictors and use of aspiration technique, respectively. 22% of respondents identified the toxicity of bupivacaine. 64% of respondents considered the safety of either root canal irrigants or intra-canal medicaments. The obturation materials were considered safe by 74% of respondents. 49% of respondents indicated the safety of radiographic examination among which 67% preferred RVG technique. 58% of respondents preferred acetaminophen for pain control. Dental interns and general dentists in Zliten exhibited a sufficient knowledge regarding the safety of endodontic treatment during pregnancy and required to improve their knowledge particularly regarding the safety of some local anaesthetics and radiographic examination during endodontic treatment. الهدف من هذه الدراسة هو تقييم معرفة أطباء الاسنان المتدربين والعموميين بشأن المعالجة اللبية للمرضى الحوامل في زليتن – ليبيا .أجريت هذه الدراسة الوصفية المقطعية باستخدام استبيان ذو نهاية مغلقة وذاتي ألإدارة جرى تعميمه على 127 من المتدربين في طب الأسنان وأطباء الأسنان العموميين في زليتن - ليبيا. يشتمل الاستبيان علي بنود ديموغرافية وأسئلة تتعلق بالجوانب المختلفة التي تختص بمعرفة المشاركين بشأن المعالجة اللبية أثناء الحمل. تم تحليل البيانات باستخدام .SPSS 26 أشار %84 من المشاركين في الدراسة الاستقصائية إلى أن الفصل الثاني من الحمل هو الفترة الأكثر أماناً للمعالجة اللبية. أكد 95% من المشاركين في الاستبيان حاجة المرضي الحوامل الي الجلوس في وضعية خاصة علي كرسي الاسنان بينما 58% منهم تعرف علي وضعية الجلوس الصحيحة. 72% و 65% من المشاركين بالدراسة اختاروا الامان للمخذر الموضعي المحتوي علي قابض للأوعية واستخدام تقنية السحب, علي التوالي. 22% من المستجيبين للدراسة تعرفوا علي سمية bupivacaine و 64% اعتبروا ان غسولات القنوات اللبية والعلاجات الداخلية للقنوات مواد امنة. مواد حشو العصب اعتبرت امنة من 74% من المشاركين. 49% من المشاركين اختاروا ان استخدام الفحص الاشعاعي هو امن وفضل 67% منهم اختبار ال RVG. 58% من المشاركين بالدراسة فضلوا وصف acetaminophen لعلاج الالم للمرضي الحوامل. المعرفة لأطباء الاسنان المتدربين والعموميين بشان المعالجة اللبية الامنة خلال فترة الحمل تعتبر كافية ولكن هناك حاجة لتطوير هذه المعرفة خاصة فيما يتعلق بمدي امان بعض مواد التخذير الموضعية والكشف الاشعاعي خلال المعالجة اللبية